Legal Issues of Financial Support for the Creation of High-Tech Industries with the Participation of Scientific Institutions in Ukraine - Hlibko, S.; Chubenko, V. (НДІ ПЗІР НАПрН України, 2022)
In the conditions of martial law on the territory of Ukraine, taking into account the fact that a large part of the industrial and agricultural complex of Ukraine has been destroyed as a result of military operations, the transformation of the economy of our state is extremely important. It has been established that the key driver of economic growth of any state is high-tech production. Under such conditions, an important step for Ukraine today and in the post-war period is the reorientation of the economy from raw materials to high-tech. The main role in the creation of high-tech products is played by financial instruments and the presence of research and development potential in the economic entity or the possibility of obtaining such services from specialized institutions. The procedure for providing financial support for the creation of high-tech industries with the participation of higher education institutions and scientific institutions on the terms of co-financing, the draft of which was proposed by the Ministry of Education and Science of Ukraine, is designed to ensure access to the specified tools. This project is the first regulatory act in Ukraine, the purpose of which is to determine the conditions for providing financial support in the form of a grant for the creation of high-tech industries with the participation of higher education institutions and scientific institutions. The purpose of this article was the analysis of the draft Resolution of the Cabinet of Ministers of Ukraine “On approval of the Procedure for providing financial support for the creation of high-tech industries with the participation of higher education institutions and scientific institutions on the terms of co-financing” as an act designed to stimulate the production of high-tech products in Ukraine. In addition, the goal is to determine the advantages, as well as to outline the contradictions and gaps of the specified draft and to make relevant proposals for its improvement, using general scientific and special scientific research methods. В умовах воєнного стану на території України, враховуючи факт розрухи великої частини промислового та сільськогосподарського комплексу України внаслідок військових дій вкрай важливою є трансформація економіки нашої держави. Встановлено, що ключовим рушієм економічного зростання будь-якої держави є високотехнологічні виробництва. За таких умов, важливим кроком для України сьогодні та в післявоєнний період є переорієнтація економіки з сировинної на високотехнологічну. Основну роль в створенні високотехнологічної продукції відіграють фінансові інструменти та наявність науково-дослідного та дослідно-конструкторського потенціалу в суб’єкта господарювання або можливість отримання таких послуг від спеціалізованих установ. Порядок надання фінансової підтримки на створення високотехнологічних виробництв за участю закладів вищої освіти та наукових установ на умовах співфінансування, проект якого запропонований Міністерством освіти та науки України, покликаний в певній мірі вирішити вказані завдання. Вказаний проєкт є першим нормативно-правовим актом в Україні, метою якого є визначення умов надання фінансової підтримки у формі гранту на створення високотехнологічних виробництв за участю закладів вищої освіти та наукових установ. Метою даної статті став аналіз проєкту Постанови Кабінету Міністрів України «Про затвердження Порядку надання фінансової підтримки на створення високотехнологічних виробництв за участю закладів вищої освіти та наукових установ на умовах співфінансування» як акту, покликаного стимулювати виробництво високотехнологічної продукції в Україні. Крім того, ціллю є визначення переваг, а також викладення суперечностей, прогалин вказаного проєкту та наведення відповідних пропозицій щодо його удосконалення, використовуючи загальнонаукові та спеціальнонаукові методи дослідження.
Keywords: co-financing; grant; high-tech production; high-tech products; scientific institution; співфінансування; грант; високотехнолгічне виробництво; високотехнологічна продуція; наукова установа